2023
DOI: 10.1177/11786302231154755
|View full text |Cite
|
Sign up to set email alerts
|

Parasitic Contamination and Microbiological Quality of Commonly Consumed Fresh Vegetables Marketed in Debre Berhan Town, Ethiopia

Abstract: Parasitic and microbial contamination and the pattern of occurrence of the parasite species depends on weather conditions, socio-cultural conditions, sampling season, analyzed vegetable products, and other factors. Therefore, local assessment of vegetable contamination is crucial for targeted and effective interventions. A cross-sectional study was conducted from February to August 2022. A questionnaire was used to assess factors associated with parasite contamination of vegetables during the marketing period.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
3
4
1
2
Order By: Relevance
“…In the present study, a higher contamination rate of vegetables was observed with Ascaris lumbricoides, a nding that closely resembles the results reported in Egypt [10], however, these rates are higher than the results of the study in Sudan [16] but lower than the ndings of the Asfaw research team in Ethiopia [4]. Regarding Enterobius vermicularis, our research revealed lower contamination rates than those reported in Egypt [10], but higher rates compared to the results in Ethiopia [4]. In the current study, the identi cation of Hymenolepis nana was less frequent than the ndings reported by Bekele and Shumbej 2019 [5].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In the present study, a higher contamination rate of vegetables was observed with Ascaris lumbricoides, a nding that closely resembles the results reported in Egypt [10], however, these rates are higher than the results of the study in Sudan [16] but lower than the ndings of the Asfaw research team in Ethiopia [4]. Regarding Enterobius vermicularis, our research revealed lower contamination rates than those reported in Egypt [10], but higher rates compared to the results in Ethiopia [4]. In the current study, the identi cation of Hymenolepis nana was less frequent than the ndings reported by Bekele and Shumbej 2019 [5].…”
Section: Discussionsupporting
confidence: 86%
“…Regarding helminth species, Ascaris lumbricoides was found in relatively high percentages in parsley (19%) and radish (14.3%), while it was not detected in pepper and coriander. These results differ from the ndings of Bekele and Shumbej 2019 [5] and Asfaw et al 2023 [4], where Ascaris lumbricoides was reported in higher percentages in lettuce and pepper. In our study, Enterobius vermicularis was found in a higher percentage in lettuce (15%), which differs from the results of Eraky et al 2014 [10], where a higher percentage of Enterobius vermicularis was reported in parsley.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…dispar (29.4%) being the most frequent, followed by Entamoeba coli (11.8%) and Giardia lamblia (6.1%) [43]. Most studies of parasite contamination of fruits and vegetables in developed countries reveal high contamination with common intestinal parasites of medical importance to humans [16,34,44].…”
Section: Intestinal Parasite Contamination Of Fruits Andmentioning
confidence: 99%
“…Consumir vegetales frescos es esencial para una alimentación balanceada. No obstante, su contaminación, especialmente por coliformes y E. coli, puede originar enfermedades gastrointestinales, clasificadas entre las Enfermedades Transmitidas por Alimentos (ETAs) (7,8).…”
Section: Introduciónunclassified